The behaviour of Reinforced Concrete Beams by Using Expanded Polystyrene Beads and Palm Oil Fuel Ash as Replacement Materials - M.H. Osman, M.H. Osman; L.Y. Chin, L.Y. Chin; S.H. Adnan, S.H. Adnan; M.L.M. Jeni, M.L.M. Jeni; W.A.W. Jusoh, W.A.W. Jusoh; S. Salim, S. Salim; Rahim, Nur Liza; J.J. Wysłocki, J.J. Wysłocki (2024)
The Reinforced Concrete (RC) beams containing Expanded Polystyrene Beads (EPS) and Palm Oil Fuel Ash (POFA) as sand and cement replacement with a percentage between 10% and 30%were studied in terms of load-deflection behaviour. RC beam’s size was 1000×150×150 mm and simply supported at spaced 750 mm apart. The 10% of POFA without EPS shows a slight increase which is 0.26% higher than normal concrete in compressive strength. The ultimate load and flexural performance of RC beams with EPS and POFA exhibited a decreasing trend. All beams’ ultimate load exceeds the design value. The cracks of the RC beam may be classified as vertical flexural cracks, and some of the cracks can be classified as shear cracks based on the crack angle. As the percentage of EPS and POFA increases above 20% for all specimens, cracking starts to change to shear cracking.